The Effect of Natuzyme in the Diets Containing Non-Starch Polysaccharides on Meat Quality of Native Chicken - Suhermiyati, S; Iriyanti, N (ANIMAL PRODUCTION, 2011)
Abstract. The purpose of this research was to determine the effect of the use of Natuzyme in feed containing non-starch polysaccharides on the quality of chicken meat. Materials used were 71 native hens of 18 week-old. The experiment was conducted using Completely Randomized Design (CRD), 3 x 3 factorial pattern. Each treatment was repeated three times and was tested further with Duncan t test. The first treatment was the use of non-starch polysaccharides (R) with the levels of 0, 5 and 10%. The second treatment was the use of Natuzyme (S) with the levels of 0, 0.1 and 0.2%. The variables measured were: energy consumption, fat consumption, carcass weight, meat glycogen, meat fat, and cholesterol of meat. The results showed that the treatments did not significantly affect energy consumption, fat consumption, carcass weight and fat content of meat. The use of non-starch polysaccharides did not significantly affect the levels of meat glycogen, while the use of Natuzyme significantly affected the levels of meat cholesterol. The conclusion is that the Natuzyme only works on feedstuffs, not in the chicken digestive tract. The sources of non-starch polysaccharide in feedstuffs can be used as an energy source for chickens until a level of 10%.Key Words: Natuzyme, non-starch polysaccharides, meat quality